Strategi Pengembangan Bisnis Pada Supplier Cat Musta Paint di Arjasari Bandung - Delianti, Mirna; Herlina, Listri; Kusumawardani, Astrin (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to develop effective business strategies for Musta Paint, a paint retail business in Bandung, to address declining sales and enhance competitiveness in the digital era. Using a qualitative research approach, this study employs SWOT analysis and Quantitative Strategic Planning Matrix (QSPM) to evaluate internal and external factors influencing the business. Data were collected from Musta Paint’s operational records and observations of market dynamics, focusing on key variables such as marketing strategies, customer engagement, and competitive positioning. The analysis reveals that Musta Paint’s dependency on traditional word-of-mouth marketing limits its market reach, especially in attracting younger, digitally active consumers. Results from the QSPM indicate that optimizing digital marketing and increasing presence on online platforms are the top-priority strategies, scoring highest in potential impact. Additional strategies include product innovation, seasonal promotions, and customer loyalty programs. The findings suggest that these strategies can enhance market reach, stabilize sales, and improve the company’s competitive edge. This research offers actionable insights for Musta Paint and similar SMEs navigating the challenges of the digital marketplace